Understanding the Trisilas Culture in Sundanese Culture (A Study of Nurul-Bajan's Interpretation) - Alma Wardatul Fuadah; Kiki Muhamad Hakiki; Yoga Irawan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
Studies linking local wisdom with Qur’anic exegesis remain limited, particularly within Sundanese culture. One relevant concept is the Tri-silas values (silih asih, silih asah, silih asuh). This study examines how these values are understood in Mhd. Romli’s Tafsir Nurul-Bajan and how Sundanese philosophy aligns with Islamic teachings. Using a qualitative library-research approach and Koentjaraningrat’s acculturation theory, this research analyzes nine verses from Surah Al-Baqarah to Ali Imran: ihsan for silih asih (Al-Baqarah 2:83, 112, 195), hikmah and yu’allimu for silih asah (Al-Baqarah 2:129, 151, 269; Ali Imran 3:48, 79), and birrun and yunfiqu for silih asuh (Al-Baqarah 2:177, 215). The findings show that Tri-silas aligns with Islamic ethics of compassion, education, and social solidarity. The social-ethical orientation (adab ijtima’i) of Nurul-Bajan demonstrates how Sundanese cultural values can serve as an effective contextual medium for Qur’anic da’wah. The novelty of this research lies in its systematic mapping between Sundanese philosophical values and Qur’anic ethical concepts, strengthening the discourse on Nusantara Qur’anic exegesis, which remains understudied. Nurul-Bajan effectively presents an integration of local culture with Qur’anic messages in a contextual and accessible manner.